Technical Training of Athletes (Texas Journal of Multidisciplinary Studies, 2023)
technical training is the effort to teach an athlete the technique and to bring them to perfection. Sports technique is a way of performing sports movements, which is characterized by a certain degree of efficiency and are the possibilities of the rationality of using the athlete's psychophysics.